Molecular Characterization of a Prevalent Ribocluster of Methicillin-Sensitive Staphylococcus aureus from Orthopedic Implant Infections. Correspondence with MLST CC30 - Montanaro, Lucio; Ravaioli, Stefano; Ruppitsch, Werner; Campoccia, Davide; Pietrocola, Giampiero; Visai, Livia; Speziale, Pietro; Allerberger, Franz; Arciola, Carla Renata (Frontiers in Cellular and Infection Microbiology, 2016)
ABSTRACT Staphylococcus aureus is the leading etiologic agent of orthopedic implant infections. Here a ribocluster of 27 S. aureus strains underwent further molecular characterization and subtyping by multilocus sequence typing (MLST) and spa-typing. This cluster had been detected by automated ribotyping (with EcoRI as restriction enzyme) of 200 S. aureus isolates from periprosthetic infections come for revision at the Rizzoli Orthopaedic Institute. The ribocluster, consisting of agr type III isolates, with a 74% co-presence of bone sialoprotein-binding (bbp) and collagen-binding (cna) genes, turned out devoid of mecA and IS256 and exhibited a high prevalence of toxic shock syndrome toxin gene (tst, 85%). Sequences achieved by spa typing and MLST were analyzed by BURP and goeBURST. Two predominant spa types, t012 (32%) and t021 (36%), and one predominant sequence type, ST30 (18/27, 67%), a Staphylococcus aureus lineage spread worldwide and regarded as the ancestor of MLST CC30, were identified. Two new sequence types (ST2954, ST2960) and one new spa type (t13129) were detected for the first time. BURP clustered the isolates into two spa clonal complexes, CC021/012 (22/27, 81%) and CC166 (4/27, 15%), plus one singleton, while goeBURST recognized solely MLST CC30. Interestingly, the 27-strains cluster detected by ribotyping corresponded exactly to CC30.